Serum Ferritin Levels Are Positively Associated With Metabolically Obese Normal Weight: A Nationwide Population-Based Study. Issue 52 (December 2015) - Kim, Jae-Woo; Kim, Do Hoon; Roh, Yong Kyun; Ju, Sang Yhun; Nam, Hyo-Yun; Nam, Ga-Eun; Kim, Dong-Won; Lee, Seung-Hyun; Lee, Chung-Woo; Han, Kyungdo; Park, Yong-Gyu
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The purpose of this study was to examine the relationship between serum ferritin levels and metabolically obese normal weight (MONW) and to determine the appropriate cut-off value of serum ferritin for the prediction of clinical metabolic status in nonobese Korean adults. Data from 9411 participants in the fourth (2008) and fifth (2010) annual Korea National Health and Nutrition Examination Surveys were used in this study. MONW was determined by combining National Cholesterol Education Program Adult Treatment Panel III criteria, Wildman criteria, and homeostatic model assessment criteria for metabolic healthy obesity. The mean serum ferritin level was 103.5 ± 1.2 ng/mL in men and 45.5 ± 0.6 ng/mL in women. The estimated cutoff value of serum ferritin for the prediction of MONW was 127.03 ng/mL in men and 46.87 ng/mL in women. Both men and women who had higher serum ferritin levels than the cutoff value had a higher prevalence of MONW than those individuals who had lower serum ferritin levels than the cutoff value. In the final multivariable adjusted logistic regression model, the odds ratio (95% confidence interval) of MONW in the subjects who had higher serum ferritin levels than the cutoff value was 1.631 (1.312–2.028) in men and 1.298 (1–1.685) in women. In this study, serum ferritin levels were positively associated with MONW, and those subjects who had higher serum ferritin levels than the cutoff value had a higher prevalence and a higher adjusted odds ratio for MONW despite being nonobese.